A queuing model‐based approach for the analysis of transactional memory systems. (10th July 2012) - Yu, Xiao; He, Zhengyu; Hong, Bo; Schulze, Bruno; Rebello, Vinod; Moreira, Jose
SUMMARY In this paper, we develop an analytical model of the execution efficiency of transactional memory (TM) systems. This model employs queuing theory to analyze the impact of an essential set of TM design parameters including the conflict rate, number of conflict detection/resolution points, and implementation overhead. The model is validated via extensive experiments. To demonstrate the effectiveness of the model, we further study the performance impact of two factors. Our study shows that, for a given TM‐based program, the frequency of performing conflict detection can be carefully chosen to minimize the mean transaction completion time. Our study also demonstrated the importance of reducing implementation overhead. We expect our study to be useful for designing TM systems and applications. Copyright © 2012 John Wiley & Sons, Ltd.